If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2y + -7) + -1y = -3y + 15 Reorder the terms: -5(-7 + 2y) + -1y = -3y + 15 (-7 * -5 + 2y * -5) + -1y = -3y + 15 (35 + -10y) + -1y = -3y + 15 Combine like terms: -10y + -1y = -11y 35 + -11y = -3y + 15 Reorder the terms: 35 + -11y = 15 + -3y Solving 35 + -11y = 15 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 35 + -11y + 3y = 15 + -3y + 3y Combine like terms: -11y + 3y = -8y 35 + -8y = 15 + -3y + 3y Combine like terms: -3y + 3y = 0 35 + -8y = 15 + 0 35 + -8y = 15 Add '-35' to each side of the equation. 35 + -35 + -8y = 15 + -35 Combine like terms: 35 + -35 = 0 0 + -8y = 15 + -35 -8y = 15 + -35 Combine like terms: 15 + -35 = -20 -8y = -20 Divide each side by '-8'. y = 2.5 Simplifying y = 2.5
| [x-9]=15 | | 4-2y=-10 | | 5x+7+x=8x-26 | | 24=-12 | | 5*tanx*cosx=4 | | x^2+y^2-4x-12y+36=0 | | xxx+xx-x-1=0 | | 1.1x=12.1 | | 8wd^4-8wh^4= | | 3x-6=5(x+4) | | ln(8x^2+10x)-ln(2x)=4 | | d=-16t^2+196 | | -10+3xy-3xy+y^2+10-y^2= | | t(2)=4.5(2)-8 | | 7n-22=-46 | | -6x-2y=-12 | | ln(8x+9)=13 | | -1/6x=16 | | 2y^2+30y-3y^2+4y-14-y= | | -8x=112 | | 3st^4-3sk^4= | | 8x-4x+3=x-7+10 | | 1/3t=17 | | 2x+4x^2-6x^2-9+1-x-3x= | | 1/2m=25 | | n/5=1.1 | | 39=45x | | t/6=13 | | 11-1c/2=60 | | 1/3(6x-21)-4(x-20) | | 9000=l(l-45) | | 2(8t*9)+4(10-16t)=20 |